Determination of Fault Type of Lombok Earthquakes from July 1 to December 31, 2018, using Focal Mechanism Method - Wardani, Ni Nyoman Susi Kesuma; Suarbawa, Komang Ngurah; Kusnandar, Ridwan (BULETIN FISIKA; Vol 22 No 2 (2021): BULETIN FISIKA August Edition, 2021)
Research has been conducted on determining the type of fault in Lombok earthquake on July 1 to December 31 2018 using the focal mechanism method. The focal mechanism is a method of reviewing fault parameters that include strike, dip and rake based on the initial movement direction of P wave recorded by the station, which then projected into a focal ball. There are 246 stations are used in several countries. There were 139 earthquakes with M?4.0 on July 1 to December 31 2018, at coordinates 7.0? S-9.0? S and 115.5? E-117.5? E. The result of fault field parameters is at nodal 1 strike=52?-149?, dip=6?-75?, rake=39?-143? and at nodal 2, strike=233?-313?, dip=18?-84?, rake=58?-119?, then projected into focus ball. Based on these results shows that earthquakes occur as a result of thrust fault movement.